2014
DOI: 10.1111/cns.12286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tacrine‐3‐caffeic Acid, A Novel Multifunctional Anti‐Alzheimer's Dimer, Against Oxidative‐Stress‐Induced Cell Death in HT22 Hippocampal Neurons: Involvement of Nrf2/HO‐1 Pathway

Abstract: Taken together, these results clearly demonstrate that T3CA protects neurons against OS-induced cell death partially through Nrf2/ARE/HO-1 signaling pathway, which further supports that T3CA might be a promising novel therapeutic agent for OS-associated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…This indicates that elevation of HO-1 level is not the primary factor contributing to its acute protective effect. These data are similar to those from previous studies showing the time course of increased expression of SOD2 and HO-1 (Chao et al, 2014) in response to other polyphenols, suggesting that this temporal profile is a generalizable phenomenon. For simultaneous treatment of HT-22 cells with glutamate and tBHQ, both SOD2 and HO-1 expression were increased before cell death, which allows either or both to protect cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that elevation of HO-1 level is not the primary factor contributing to its acute protective effect. These data are similar to those from previous studies showing the time course of increased expression of SOD2 and HO-1 (Chao et al, 2014) in response to other polyphenols, suggesting that this temporal profile is a generalizable phenomenon. For simultaneous treatment of HT-22 cells with glutamate and tBHQ, both SOD2 and HO-1 expression were increased before cell death, which allows either or both to protect cells.…”
Section: Discussionsupporting
confidence: 90%
“…This indicates that, within 3 hours after application, tBHQ efficiently maintains mitochondrial function and further prevents cell damage. Upregulation of HO-1 expression has been shown to prevent glutamate-induced oxidative toxicity in HT-22 cells (Rössler et al, 2004;Son et al, 2013;Chao et al, 2014). However, the temporal profile of expression of SOD2 and HO-1 shows that peak SOD2 expression occurs at 3 hours but HO-1 expression does not peak until 12 hours following exposure to tBHQ (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In an earlier study decreased NF-kB activation was detected in brusatoltreated HL-60 cells when exposed to significantly higher (micromolar) concentrations [2]. An inhibitory effect of brusatol on the transcription factor Nrf2 is well established and has been demonstrated in cell lines such as A549, HT22, Hepa-1c1c7 [3,14,15], and in bTC6 (our unpublished data). Nevertheless, Nrf2 downregulation is unlikely to mediate the anti-iNOS activity of brusatol since the Keap1/Nrf2 system is not implicated in regulation of iNOS expression.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, CDDOmethylamide, a potent activator of Nrf2 signaling, significantly improves spatial memory retention and reduces plaque burden, Ab 1-42 levels, microgliosis and oxidative stress in Tg19959 mice, which carry the human amyloid precursor protein with two mutations [22]. Recently, Chao et al [23] reported that tacrine-3-caffeic acid, a novel promising multifunctional dimer against AD, could protect neurons against glutamate-induced cell death partially through Nrf2/ARE/HO-1 signaling pathway. These studies support a protective role of Nrf2 pathway in AD cellular and animal models and provide an emerging avenue for the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%